Economic Criminology: Bridging disciplinary and professional silos in countering economic crime - Branislav Hock; Nicholas Ryder (Journal of Economic Criminology, 2023)
The Journal of Economic Criminology aims to facilitate discussion among different academic disciplines and practice areas on how people should work together to better understand and address economic crime problems. In this editorial to the very first volume of the journal, Editors in Chief discuss their view of the economic criminology framework and how to make it a living concept. The framework is about an interface between disciplines studying economic crime. Economic criminology requires people, called ‘economic criminologists’, to be open to experiment and reflect upon the value of other disciplines in their own research and policing practice. This also requires a reflection upon different styles of undertaking research and writing academic works